2012
DOI: 10.1021/ma202084m
|View full text |Cite
|
Sign up to set email alerts
|

Mesogen-Driven Formation of Triblock Copolymer Cylindrical Micelles

Abstract: Evidences were gathered to support mesogen-driven formation of cylindrical micelles from BCF and ACF triblock copolymers. Here A, B, C, and F denote poly(acrylic acid), poly(tert-butyl acrylate), poly(2-cinnamoyloxylethyl methacrylate), and the liquid crystalline poly(perfluorooctylethyl methacrylate) block, respectively. At room temperature (21 °C) in all tested solvents that were selective for the A or B blocks, three of the four copolymers with various compositions formed exclusively cylindrical micelles po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
92
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 78 publications
(95 citation statements)
references
References 79 publications
3
92
0
Order By: Relevance
“…The cylindrical morphology was further confirmed by scanning electron microscopy (SEM) characterization in Figure S13 (Supporting Information). Such peculiar self‐assembly behavior is originated from the liquid crystalline (LC) ordering of PFOEMA, which was reported to form smectic phase liquid crystals by our group and others . Different from the self‐assembly of coil–coil block copolymers, which tends to spherical nanoparticles, the smectic LC ordering of PDMA‐ b ‐PFOEMA assemblies entails the layered stacking of the polymer chains, favoring the formation of cylindrical micelles …”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…The cylindrical morphology was further confirmed by scanning electron microscopy (SEM) characterization in Figure S13 (Supporting Information). Such peculiar self‐assembly behavior is originated from the liquid crystalline (LC) ordering of PFOEMA, which was reported to form smectic phase liquid crystals by our group and others . Different from the self‐assembly of coil–coil block copolymers, which tends to spherical nanoparticles, the smectic LC ordering of PDMA‐ b ‐PFOEMA assemblies entails the layered stacking of the polymer chains, favoring the formation of cylindrical micelles …”
Section: Resultsmentioning
confidence: 91%
“…Besides, M n of these block copolymers increases with the monomer conversion, and the dispersities are <1.30 for all the copolymers (Figure c). However, because of the strong associative interactions among the fluoro‐containing blocks, the solubility of PFBEMA decreases with the chain length of PFBEMA, leading to an increscent deviation between the theoretical and the actual M n . DLS studies indicate that after 3 h of polymerization, aggregates of 15 nm formed.…”
Section: Resultsmentioning
confidence: 99%
“…[16,23] Therefore,w ei magined that at remendous pressure was required to force water into af luorinated capsule that might bear molecular defects with sizes smaller than 1nm. To verify our hypothesis,w ep repared water-dispersible nanocapsules with af luorinated internal lining from the triblock terpolymer ACF, [24] where A, C, and Fd enote poly(acrylic acid), poly(2-cinnamoyloxyethyl methacrylate), and poly(2-perfluorooctylethyl methacrylate), respectively ( Figure 1a). To verify our hypothesis,w ep repared water-dispersible nanocapsules with af luorinated internal lining from the triblock terpolymer ACF, [24] where A, C, and Fd enote poly(acrylic acid), poly(2-cinnamoyloxyethyl methacrylate), and poly(2-perfluorooctylethyl methacrylate), respectively ( Figure 1a).…”
mentioning
confidence: 94%
“…Figure 2 shows aT EM and an AFM height image of the ACF nanocapsules after they had been sprayed and dried on ac ellulose-coated TEM grid and on as ilicon wafer, respectively.The observation of the dark rings with agray center by TEM, [31] and of collapsed bowls by AFM, [25] as well as the large diameter of the particles relative to the length of the fully stretched ACFc hains support the targeted capsular structure (Figure 2). [24] Successful capsule and nanobubble preparation was also confirmed by data shown in Table S2 (Supporting Information). These fine structures should be due to the uneven distribution of the poly(sodium acrylate) chains on the capsular surfaces because similar structures were observed for ACFcylindrical micelles after their surface Achains were stained by uranyl acetate.…”
mentioning
confidence: 98%
“…The solution self-assembly of amphiphilic "coil-coil" diblock copolymers, where both blocks are amorphous and behave as random coils in solution has been well studied and offers an important "bottom-up" route to nanoscale soft materials with applications such as drug delivery vehicles, nanoreactors, templates, and stimuli-responsive has been demonstrated for a wide variety of asymmetric diblock copolymers containing crystallizable core-forming segments including polyethylene, [ 8,[17][18][19] poly(ethylene oxide), [ 20 ] poly(ε-caprolactone), [ 21,22 ] poly(ε-caprolactoneb -L -lactide), [ 23 ] polylactide, [ 7,24 ] polyacrylonitrile, [ 25 ] poly(ferrocenyldimethylsilane) (PFS), [ 26,27 ] poly(ferrocen yldimethylgermane), [ 28 ] poly(ferrocenyldiethylsilane), [ 29 ] poly(perfl uoro-octylethylmethacrylate), [ 30 ] cyclic polypeptoids, [ 31 ] and even smectic liquid crystalline polymers. [ 32 ] In several cases, it has been demonstrated that the dimensions of micelles formed by CDSA can be controlled by a living process analogous to a living covalent polymerization.…”
Section: Introductionmentioning
confidence: 99%